2020
DOI: 10.4103/jpbs.jpbs_113_20
|View full text |Cite
|
Sign up to set email alerts
|

Oral health–related quality of life in children and adolescents of Indian population

Abstract: A BSTRACT Background: Kids and teenagers are more prone to oral diseases. Poor oral health has a significant impact on oral well-being–associated quality of life. Thus, we performed an investigation to examine the outcome of oral health status on the quality of life of children and adolescents in Indian population, by using the Oral Health Impact Profile-14 (OHIP-14). Materials and Methods: A total of 100 children, ranging between 1 and 19 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In fact, previous caries experience has been shown to be the most important predictor of poor oral quality of life, not only in the paediatric population [42,43]. A study conducted by Sinha et al in 2020 in Indian children and adolescents has already indicated a clear association between poor oral health and impaired quality of life [44]. In this way, studies could continue beyond a cross-sectional study such as this one and be examined longitudinally over time.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, previous caries experience has been shown to be the most important predictor of poor oral quality of life, not only in the paediatric population [42,43]. A study conducted by Sinha et al in 2020 in Indian children and adolescents has already indicated a clear association between poor oral health and impaired quality of life [44]. In this way, studies could continue beyond a cross-sectional study such as this one and be examined longitudinally over time.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, our app can be beneficial for all users, especially those who do not work in a health‐related occupation, for the maintenance and improvement of oral health‐related quality of life. Moreover, the quality of life related to oral health, which was examined using the OHIP‐14, was significantly associated with oral hygiene practice, such as toothbrushing habits (Avasthi et al, 2022 ; Sinha et al, 2020 ). Therefore, the quality of life related to oral health may have affected the oral health practices of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Gene editing technology, with its ability to identify, delete, or replace genes can improve the prognosis of Squamous cell carcinoma of the oral cavity that arises due to viral and bacterial factors. 49,50,51…”
Section: Advances In Gene Editing Toolsmentioning
confidence: 99%